2023
DOI: 10.1021/acs.cgd.3c00366
|View full text |Cite
|
Sign up to set email alerts
|

Computational Simulation of CO2/CH4 Separation on a Three-Dimensional Cd-Based Metal–Organic Framework

Abstract: Natural gas purification and biogas recovery require efficient separation of CO2 from CH4, as CH4 is increasingly being recognized as a promising substitute for petroleum due to its environmentally sustainable nature, abundance in natural resources, and economic benefits. In the present work, a 3D Cd-based metal–organic framework, [Cd2(DBrTPA)2(DMF)3] (MUT-11) 2,5-[dibromoterephthalic acid (DBrTPA) and dimethyl formamide (DMF)] was synthesized using a combination of different synthetic methods and fully charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 124 publications
(160 reference statements)
0
2
0
Order By: Relevance
“…Consequently, it has become increasingly important to find alternative energy sources and solutions to reduce carbon dioxide . Biogas is a renewable energy source made primarily from CH 4 , CO 2 , and minor gases (N 2 , H 2 S). , Biogas treatment and separation of CO 2 before use for transportation prevents pipe corrosion and release of CO 2 into the atmosphere . Additionally, CO 2 /N 2 separation plays a significant role in reducing the amount of greenhouse gases released into the atmosphere from flue gases .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it has become increasingly important to find alternative energy sources and solutions to reduce carbon dioxide . Biogas is a renewable energy source made primarily from CH 4 , CO 2 , and minor gases (N 2 , H 2 S). , Biogas treatment and separation of CO 2 before use for transportation prevents pipe corrosion and release of CO 2 into the atmosphere . Additionally, CO 2 /N 2 separation plays a significant role in reducing the amount of greenhouse gases released into the atmosphere from flue gases .…”
Section: Introductionmentioning
confidence: 99%
“…2 MOFs have intriguing characteristics such as high porosity, large surface area, crystalline structure, tunable pore structure, stable chemical and thermal properties, and ability to tune optical properties through organic ligands, metal nodes, and guest molecules. 1–8 Due to their fascinating properties, MOFs have applications in numerous fields, including gas storage/separation, 7–11 sensing, 12 drug delivery, 13–20 antibacterial agents, 21–26 templates, 27–29 catalysis, 30,31 and photocatalysis. 1,2,29,32,33…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to conventional porous materials, MOFs offer several notable advantages, including high specific surface area and porosity, low crystal density, tunable pore sizes, multifunctionality (owing to the wide variety of possible arrangements of metals and ligands), enabling precise modulation of their physicochemical properties for specific applications, and favorable biocompatibility. Recently, a variety of applications of these compounds have been documented in different fields, including catalysts, sensing, gas storage, antibacterial properties, and especially drug delivery. The fascinating characteristics of MOFs, including exceptional stability, significant surface area, controllable functionalization, and the ability to incorporate functional groups, have rendered them highly appealing for utilization as carriers in drug delivery applications. The encapsulation of quercetin into the UiO-66 structure provided a synergetic dual sensitizing effect, demonstrating a loading of 20.7% . Another study found that FA-BSA/CuS@ZIF-8 has about 24% drug-loading capacity toward quercetin .…”
Section: Introductionmentioning
confidence: 99%